2003
DOI: 10.3758/bf03194842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison is not just subtraction: Effects of time- and space-order on subjective stimulus difference

Abstract: In five experiments, participants made comparative judgments of paired successive or simultaneous stimuli. Time- or space-order errors were obtained, which varied with the interstimulus interval (ISI) or stimulus duration, as well as with the stimulus level. The results, in terms of scaled subjective differences, are well described by Hellström's (1979) sensation-weighting model. With successive presentation, in comparisons of line length and tone loudness, the first stimulus had the greater weight in determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
153
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(174 citation statements)
references
References 60 publications
(115 reference statements)
17
153
4
Order By: Relevance
“…Stevens (1957) included the existence of TOE as one of the criteria for labeling an attribute as prothetic. There is, therefore, a certain circularity in saying that the TOE has been found for all prothetic scales studied, but it is certainly true that this effect has been obtained for all of those scales that have been thought to be prothetic for other reasons (Hellström, 2003). Here, we studied the NEM only for audition, but because of the relation that the TOE has to NEM, we suspect that similar results will be found with other prothetic attributes.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Stevens (1957) included the existence of TOE as one of the criteria for labeling an attribute as prothetic. There is, therefore, a certain circularity in saying that the TOE has been found for all prothetic scales studied, but it is certainly true that this effect has been obtained for all of those scales that have been thought to be prothetic for other reasons (Hellström, 2003). Here, we studied the NEM only for audition, but because of the relation that the TOE has to NEM, we suspect that similar results will be found with other prothetic attributes.…”
Section: Discussionmentioning
confidence: 83%
“…Hellström (2003) lamented how relatively little work had been carried out on the TOE phenomenon. Indeed, we were quite surprised to realize how dramatic these effects can be, and so we second Hellström's (2003) sentiment, adding that these effects are probably only ignored at the peril of arriving at erroneous conclusions. We came to realize that both the definition of the TOE and the prevailing practice of averaging over individual data has precluded the study of a much more fundamental phenomenon: When a respondent provides a perceptual "match" between two successively presented signals differing in intensity only, in general, the signals are not physically identical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we describe an alternative strategy successfully used for this purpose on numerous occasions (e.g., , 2009a; García-Pérez, Alcalá-Quintana, Woods, & Peli, 2010) and that takes advantage of a response format that has also been used for other purposes (García-Pérez, 2010;Hellström, 2003;Kaernbach, 2001;Poggel, Strasburger, & Mac Keben, 2007;van Vleet & Robertson, 2006;von Waldkirch, Lukowicz, & Tröster, 2004. This strategy consists of three steps.…”
Section: A Model Of Response Bias and How To Eliminate Itmentioning
confidence: 99%
“…Lapid et al also reported evidence to the effect that discrimination performance in the reminder task is significantly better when the standard stimulus is presented in the first interval than when it is presented in the second, and proposed a moving-average model to explain some of their results. In particular, the model explains the time-order effect (i.e., differences in performance associated with presentation order) through a sensation-weighting rule analogous to that proposed by Hellström (1979Hellström ( , 1985Hellström ( , 2003 but in which the observer is further assumed to use an implicit standard that is continuously updated through sensory experience gathered along a subset of the immediately preceding trials.This article reanalyzes the data from Lapid et al's (2008) experiments, with two goals. Our first goal is to correct an error in their estimates of the DL from the 2AFC task.…”
mentioning
confidence: 99%